Kemiskinan Dan Reorientasi Pemikiran Ekonomi - Iskandar Iskandar (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
There were hundreds of programs nowadays that were carried out for weak and poor groups. Respectively the Department of the government had various programs for these weak and poor groups. However, according to Prof. Mubyarto’s statement that was very rare today not the matter of the fund but the matter of the interest in the poor group. The standard measurement of the interest definitely not in the volume and the number of voices like in the General Election campaign, but his actualization. In this case, the social interest not only came from the government but also from all over the social stratum. Key Word : Kemiskinan, Reorientasi